What is a Caucasian 'fine' hair? Comparing instrumental measurements, self‐perceptions and assessments from hair experts. (26th April 2016) - Bouabbache, S.; Galliano, A.; Littaye, P.; Leportier, M.; Pouradier, F.; Gillot, E.; Panhard, S.; Loussouarn, G.
Abstract: Objective: To determine the various factors contributing to what Caucasian women describe as 'fine hair'. Methods: Three complementary approaches were used, namely self‐evaluation by the volunteer, assessment by a sensorial expert and instrumental measurements, in order to determine some of the possible parameters taken into account by Caucasian women when they describe the notion of fine hair. One hundred fifty one women of Caucasian origin participated in the study. They varied in age, and varied in that some considered themselves as having fine hair, and others not. The instrumental measurements carried out included hair diameter measurements, hair density measurements, hair breakage force, hair flexibility and scalp sebum levels. Results: From six parameters defined initially, four parameters were found to be in common with the three approaches: hair abundance (density), hair thickness, hair resistance and the volume of the hair on the head. The commonly used term 'body' was only common to self and expert evaluation, whereas the influence of curliness was only common to expert evaluation and instrumental measurements. Conclusions: This study has shown close agreement between sensorial and instrumental findings, and also illustrates how the women participating can subtly and adequately describe their own hair. It is important to note that the words 'fine hair' describes a lot more than just physically thin hair fibres. Ageing is an additional factor that clearly impacts certain parameters associated with 'fine hair' among the volunteers. Abstract : The present work allows to go further in the understanding of fine hair perception by Caucasian women through an objective and multidisciplinary characterization. A quantitative study based on sensorial and instrumental assessment was done in parallel of a consumer self‐evaluation. The population with fine hair perception is described through six main parameters which allow to take into account the consumer expectations.